Green Bonds: Ownership, Friendship, and Kinship in Eighteenth-Century British Gardens - Châtel, Laurent (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2020)
This article sets out to recapture a sense of the collective and collaborative approach to gardening, arguing that the study of intermediality in the context of eighteenth-century British gardens is not just about the melting pot of sister arts, but also the meeting place of sisters-and-brothers-in-arts, painters, poets, amateurs, patrons, and professionals alike finding themselves connected in and through gardens—a shift of emphasis onto the human relations and brotherliness forged through the arts, which contributes to the social history of gardens.